Identifikasi Aliran Energi Listrik pada Mesin CNC Machining Center - Harbintoro, Sony; Srimurni, Rafika Ratik (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
CNC machine tools have been widely used in the process and manufacturing industries, which have the potential to increase the intensity of electrical energy consumption so that energy efficiency is needed. Energy efficiency is a necessity for the sustainability of the process and manufacturing industrial sector which will be related to energy costs and environmental factors. In order to carry out energy efficiency, it is necessary to identify the consumption of electrical energy by tracing and mapping the electrical energy flow to the components in a CNC machining center machine, so opportunities for energy savings can be known. This research was conducted by collecting data by monitoring energy consumption in stand-by, setting and cutting machine conditions. Cutting tests are carried out to determine the energy consumption of each machine component that affects energy use. After that it can be seen the energy flow pattern by classifying the energy user components into primary and secondary components. Based on the analysis of electrical energy consumption data during the cutting process, it is known that the significat energy users are the spindle motor, the axis feed motor (X, Y, Z) and the coolant motor.